2017
DOI: 10.1080/14767058.2017.1342794
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of melatonin in the treatment of neonatal sepsis

Abstract: Melatonin could be used in the treatment of neonatal sepsis in both preterm and full-term neonates beside the conventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The increased melatonin levels are compatible with the reported disruption of circadian rhythmicity in critically ill patients [29]. Melatonin is used as a supporting drug in septic infants and could be a promising therapeutic option in sepsis patients to promote stable circadian rhythms, improve immunity and outcomes [30]. However, further research is needed to analyze the impact of the circadian rhythm on sepsis mortality and its translational potential to nd promising treatment options for improving sepsis care [31].…”
Section: Discussionmentioning
confidence: 63%
“…The increased melatonin levels are compatible with the reported disruption of circadian rhythmicity in critically ill patients [29]. Melatonin is used as a supporting drug in septic infants and could be a promising therapeutic option in sepsis patients to promote stable circadian rhythms, improve immunity and outcomes [30]. However, further research is needed to analyze the impact of the circadian rhythm on sepsis mortality and its translational potential to nd promising treatment options for improving sepsis care [31].…”
Section: Discussionmentioning
confidence: 63%
“…If we convert this murine dose to the human dose according to standard dose translation, based on dividing the surface area by a factor 12.3 (120), the calculated equivalent human dose is 8.1 mg/kg/day (100/12.3 = 8.1). This dose is very similar to the dose used in two neonatal septic trials (8.1 and 8.2 mg/kg/day), as described previously [86,87]. Importantly, this dose would not cause obvious adverse effects, based on the outcomes of these clinical trials.…”
Section: Melatonin and Its Safetymentioning
confidence: 73%
“…Melatonin has a robust antioxidant or free radical scavenging activity of [ 57 , 58 ] and melatonin administration also impairs NF-κB transcriptional activity, reducing pro-inflammatory cytokine (IL-1β, TNF-α, IFN-γ) release and inhibiting activation of the NLRP3 inflammasome [ 59 ]. Melatonin improved survival and clinical outcomes in neonates versus controls in sepsis [ 28 , 60 , 61 ]. We have demonstrated that the immunomodulatory effects of melatonin in sepsis can also be broadened to include reducing neutrophil and monocyte activation.…”
Section: Discussionmentioning
confidence: 99%